Urban Public Spaces, Public Health, and Heavy Metal Pollution Threatening in Ankara City Center: Strategies for Urban Planning - Işinkaralar, Öznur; Pi̇ri̇nç Bayraktar, Emine (Kastamonu University, 2022)
In the last century, worldwide population growth and concentration in urban areas cause many problems, especially in the central areas of metropolitan cities. One of these problems is air pollution it reduces the quality of life of the citizens and threatens public health. Among the components of air pollution, heavy metals are the most dangerous because they accumulate in metabolism, some of them are toxic and poisonous even at low concentrations, and they are deadly for human health at high concentrations. Studies on the determination of air pollution are limited to revealing the current situation and do not offer solutions for urban planning. In this context, the accumulation of copper elements, which is extremely dangerous for public health, in plants located in the city center was investigated by using landscape plants as a tool in the research. Within the scope of the study, the change of copper concentration in five plant species grown in areas with no traffic, less dense, and dense areas were investigated. As a result of the research, the increase in the concentration of copper in the air due to traffic has been revealed statistically. The research emphasizes the relationship between heavy metal pollution, which poses a serious threat to public health, and urban planning, and reveals the basic strategies in terms of urban planning.
Keywords: Engineering; Mühendislik; City centers; Urban quality of life; Public health; Air pollution; Ankara; 13. Climate action; 11. Sustainability; 15. Life on land; 12. Responsible consumption; 3. Good health